Biochemical Characterization of Partially Stabilized Parthenium hysterophorus L. and Cow Dung Consortium and Its Effect on the Growth Performance of Maize (Zea mays L.) - Shetie Gatew; Andargachew Mengistu (Applied and Environmental Soil Science)
Parthenium (Parthenium hysterophorus L.) is a major anxious weed found in pastures, wastelands, and agricultural lands. It usually competes very well and reduces crop yield. Up-rooting and herbicides have long been used as management options for weeds. However, these methods are neither economically nor environmentally sound. Another approach is to make compost of it, transforming a problem into an opportunity. Four treatments viz. Parthenium (100%) and Parthenium to cow dung ratio (75 : 25, 50 : 50, 25 : 75 w/w) were partially stabilized for 60 days under aerated conditions. The physical and chemical characteristics of partially stabilized organic materials were analyzed and the effects of the partially stabilized organic materials on the germination and growth performance of maize (Zea mays L.) were assessed. The results revealed that pH, EC, OC, OM, TN, P availability, and C/N were not significantly different; this showed an insignificant difference (P > 0.05) among the treatments. However, particle densities, P availability, EC, OC, and TN were found to be higher in 75 : 25 Parthenium cow dung ratios than in 25 : 75 ratios. Root length, shoot length, and germination index were significantly different among the treatments (P ≤ 0.05). The seed germination index of maize was the highest (113%) in 75 : 25 ratios of Parthenium and cow dung followed by 50 : 50 ratios (95%) and 25 : 75 ratios (86%); relatively, low germination indices (84.86%) were recorded from partially stabilized organic materials prepared from Parthenium alone. The findings revealed that partially stabilized Parthenium mixed with cow dung could be promising for organic farming and an option for weed management.